The Formation of the Identity of Child with the Mental Disability in the Educational Process - Rozen, Barbara (Studia Warmińskie, 2011)
The formation of the identity of child with the mental disability in the educational process is the second part of the paper, which purpose is the approximation of the fundamental truth about the person with mental disability. The realization of this truth is the task of the education. The task of the educator is to help to every child to discover and experience its dignity and to recognise its identity. The man experiences and develops himself through the relations with people and existential situations. The child with the mental disability can grow up like another children but it needs proper stimulations and good conditions to the comprehensive activity during the whole educational process. There is a very important thing to overcome the hindrances and difficulties in the educational process. The necessity of the overcoming is included in the nature of the man. The realization of this need has the influence on the proper mental activity of child. The children with the mental disability have the same psychological stages like another children. After childhood and adolescent period the child becomes adult. It is necessary to help to him in selecting of proper dress, behaviour, playing and activity in this age. The growing of independence is a very important process for the future identity. The fundamental role plays the family. If the participation in the social life completes the proper educational influence of the family, the child will experience abundance of its personality, value of life and happiness of its being.